İkinci dil olarak Türkçe öğretiminde çevrim içi dinleme stratejileri öğretimi - BENZER, AHMET (My University, 2022)
Listening strategies are enacted plans that one can use to better understand, learn, remember, and comprehend a target language. The present study aims to examine how the process of listening strategy instruction may be implemented in the teaching of Turkish to L2 learners. The study was a qualitative one, conducted with the action research method on an online platform, Zoom. Five Turkish L2 learners participated in the study. The results show that students used the listening strategies in various frequencies and combinations during the implementation process. Throughout the implementation process, the least used strategies were relating with prior information, performance evaluation, monitoring, and inferencing, while the most frequently used strategies were note-taking, determining keywords, translating, and prediction. The students stated that prediction, note-taking, and planning were the most useful strategies for them during the implementation process. Also, the use of authentic videos in online listening strategy instruction lessons contributed to students' learning in diverse areas of interest, particularly learning new vocabulary, and thus motivate them.

Dinleme stratejileri, öğrencilerin bir hedef dili daha iyi anlamak, öğrenmek, hatırlamak ve kavramak için kullanabilecekleri uygulanabilir planlardır. Bu çalışma, dinleme stratejileri öğretim sürecinin Türkçe ikinci dil öğrencileri üzerinde nasıl uygulanabileceğini incelemeyi amaçlamaktadır. Araştırma nitel desenlerden eylem araştırması yöntemiyle çevrim içi bir platform olan Zoom üzerinden gerçekleştirilmiştir. Çalışmaya ikinci dil olarak Türkçe öğrenmekte olan beş öğrenci katılmıştır. Araştırma sonuçlarına göre öğrenciler uygulama sürecinde öğrendikleri dinleme stratejilerini çeşitli sıklık ve kombinasyonlarda kullanmışlardır. Bu çalışmanın uygulama sürecinde en az kullanılan stratejiler ön bilgi ile ilişkilendirme, performans değerlendirme, izleme ve çıkarım yapma iken en sık kullanılan stratejiler sırasıyla not alma, anahtar kelime belirleme, çeviri yapma ve tahmin etme olmuştur. Öğrenciler tahmin etme, not alma ve planlamanın uygulama sürecinde kendileri için en faydalı stratejiler olduğunu belirtmişlerdir. Ayrıca çevrim içi derslerde strateji eğitiminde otantik videoların kullanılmasının, öğrencilerin farklı ilgi alanlarında, özellikle yeni kelimeler öğrenmelerine katkı sağladığını ve dolayısıyla onları motive ettiğini göstermektedir.
Online listening strategy instruction in teaching Turkish as an L2
Keywords: Listening education; listening; second language; strategy; Teaching Turkish as a second language; Dinleme eğitimi; dinleme; ikinci dil; strateji; Türkçenin ikinci dil olarak öğretimi